Factores de riesgo y su influencia en el desarrollo de complicaciones microvasculares de miembro inferior en paciente diabético tipo 2 del Hospital Básico de Yaguachi, diciembre 2022- mayo 2023. - Abero Sánchez, Nagelly Yamilex (2023)
Chronic complications due to type II diabetes mellitus usually arise from inadequate treatment of patients or from various sociodemographic and behavioral risk factors. This pathology in Ecuador is increasing, currently a prevalence of 5.7% is reported, which represents approximately 500,000 diabetic people. Objective: to determine the risk factors and their influence on the development of lower limb microvascular complications in a type II diabetic patient at the Yaguachi Basic Hospital, December 2022- May 2023. Methodology: the analytical-synthetic method was used applying a quantitative modality, being a descriptive, field and cross-sectional investigation. Data collection: the survey was used through a questionnaire of organized and structured questions. Results: data analysis was performed using the Microsoft Excel and SPSS program; obtaining as sociodemographic factors, the age group of 51-60 years (34.2%), male sex (56.3%), secondary educational level (47.9%), free union (49.3%) and suffered from hypertension arterial (37%); without harmful habits, did not drink alcohol (60.3%) and did not smoke (63%); their diagnosis was more than 10 years ago (63%) and the main condition was ulcer (53.4%). Conclusion: it was possible to establish some risk factors and their significant influence on the development of microvascular complications in the lower limb in type II diabetic patients, therefore it is considered correct that strategies focused on lifestyle modification and promotion are designed and implemented. of self-care practices.